2016
DOI: 10.1007/s10995-016-1957-5
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and Weight Status Among Women Recently Immigrating to the US

Abstract: Objective Depressive symptoms have been associated with obesity. Little is known about this relationship among immigrants. We examined relationships between depressive symptoms and weight status in immigrant women from three ethnic groups. Methods Participants were Brazilian, Haitian, and Latina women (n=345) enrolled in Live Well, a community-based, randomized intervention designed to prevent weight gain in recent immigrants. Study data are from baseline when participants completed the Center for Epidemiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 28 publications
1
16
0
3
Order By: Relevance
“…Study findings are within the range reported by previous studies in this population [ 47 , 48 , 59 , 60 ]. Prior studies have reported obesity prevalence rates ranging from 17.9% to 44.4% [ 47 , 48 ] and prevalence of elevated depressive symptoms ranging from 11.1% to 32.4% when assessed using diverse instruments and cut-off points [ 21 , 42 , 43 , 61 ], as well as the same instrument and cut-off points used in this study [ 46 , 48 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Study findings are within the range reported by previous studies in this population [ 47 , 48 , 59 , 60 ]. Prior studies have reported obesity prevalence rates ranging from 17.9% to 44.4% [ 47 , 48 ] and prevalence of elevated depressive symptoms ranging from 11.1% to 32.4% when assessed using diverse instruments and cut-off points [ 21 , 42 , 43 , 61 ], as well as the same instrument and cut-off points used in this study [ 46 , 48 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that both maternal depression and obesity are modifiable factors associated with adverse maternal and child outcomes, this finding underscores the need for assessing and addressing maternal mental health in the pre- and post-natal periods [ 8 , 35 ]. Interventions designed to reduce depressive symptoms are likely to contribute to reduction in risk of obesity and vice-versa, interventions targeted at prevention and control of obesity are likely to contribute to a reduction in the symptoms of depression [ 40 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations